2015
DOI: 10.1055/s-0034-1376189
|View full text |Cite
|
Sign up to set email alerts
|

De Novo Aneurysm Formation at the Anastomosis Site Incidentally Detected 2 Years after Single-Barrel STA-MCA Bypass Surgery: Case Report and Review of the Literature

Abstract: This case report describes the de novo aneurysm formation at the anastomosis site 2 years after single-barrel superficial temporal artery to middle cerebral artery bypass surgery. Correct bypass patency and morphology of the anastomosis site was documented intraoperatively and immediately postoperatively by indocyanine green videoangiography and digital subtraction angiography (DSA). Aneurysmatic dilatation at the anastomosis site was observed 2 years postoperatively upon computed tomography angiographic follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 21 publications
0
3
0
1
Order By: Relevance
“…[8][9][10][11] According to our knowledge, this is the first case of STA-MCA bypass aneurysm that was successfully treated through an endovascular approach. 6,[8][9][10][11][12][13][14][15][16][17][18][19] Endovascular treatment has been widely used in the setting of graft stenosis and thrombosis to reestablish flow and sustain adequate cerebral perfusion. In long-term follow-up, bypass patency is maintained in approximately 90% of cases 20 with endovascular rescue approaches in the remaining 10% in an attempt to regain adequate cerebral perfusion.…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10][11] According to our knowledge, this is the first case of STA-MCA bypass aneurysm that was successfully treated through an endovascular approach. 6,[8][9][10][11][12][13][14][15][16][17][18][19] Endovascular treatment has been widely used in the setting of graft stenosis and thrombosis to reestablish flow and sustain adequate cerebral perfusion. In long-term follow-up, bypass patency is maintained in approximately 90% of cases 20 with endovascular rescue approaches in the remaining 10% in an attempt to regain adequate cerebral perfusion.…”
Section: Discussionmentioning
confidence: 99%
“…The most common complications of end-to-side STA-MCA bypass are perioperative stroke and graft occlusion. Millesi et al [19] reported a case report of de novo aneurysm formation at the anastomosis side with a review of 17 cases published in the literature. Horiuchi et al [20] proposed a revision of the anastomosis in case of intraoperative occlusion.…”
Section: Discussionmentioning
confidence: 99%
“…Ponowne otwarcie wytworzonego zespolenia w celu do-kładnego zbadania i skontrolowania drożności naczyń, jak również zabieg ponownego zespolenia mogą się jednak wiązać z następstwami pod postacią niedrożności obu zespalanych naczyń [24,30]. Warto też wspomnieć, że jednym z pooperacyjnych powikłań STA-MCA może być także wytworzenie de novo tętniaka [31]. Ważne jest, aby u chorych poddawanych tego rodzaju rekonstrukcji stosować w okresie okołooperacyjnym leki przeciwpłytkowe oraz utrzymywać prawidłowe ciśnienie tętnicze w trakcie wykonywanego zabiegu, co zmniejsza ryzyko powikłań, a także zapewnia odpowiednią drożność wytworzonego zespolenia [32].…”
Section: Technika Sta-mcaunclassified